2021
DOI: 10.1002/smll.202104438
|View full text |Cite
|
Sign up to set email alerts
|

Phthalocyanine‐Triggered Helical Dipeptide Nanotubes with Intense Circularly Polarized Luminescence

Abstract: Nanotubes with circularly polarized luminescence (CPL) are attracting much attention due to many potential applications, such as chiroptical materials, displays, and sensing. However, it remains a challenge to change the assemblies of ordinarily molecular building blocks into CPL supramolecular nanotubes. Herein, the regulation of quite common dipeptide (Fmoc‐FF) assemblies into unprecedented helical nanotubes exhibiting intense CPL is reported by simply doping a few phthalocyanine (octakis(carboxyl)phthalocya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…The authors envisaged potential applications in biomedicine or photocatalysis. 93 Fmoc-Lys-Phe-OMe was also reported to self-assemble into NTs when templated by addition of anionic heparin. 94…”
Section: Dipeptide Nts and Their Chemical Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors envisaged potential applications in biomedicine or photocatalysis. 93 Fmoc-Lys-Phe-OMe was also reported to self-assemble into NTs when templated by addition of anionic heparin. 94…”
Section: Dipeptide Nts and Their Chemical Structuresmentioning
confidence: 99%
“…The authors envisaged potential applications in biomedicine or photocatalysis. 93 Fmoc-Lys-Phe-OMe was also reported to self-assemble into NTs when templated by addition of anionic heparin. 94 Phe-Phe has been N-capped with chromophores Cy-3 and Cy-5 to form NTs that accumulated selectively in the mitochondria of human-carcinoma cells, whose extremely negative inner membrane potential [(DC m ) cancer E À220 mV] enabled their assembly leading to apoptosis.…”
Section: N-capped Dipeptidesmentioning
confidence: 99%
“…Jiang et al synthesized CPL spiral nanotubes composed of dipeptide (Fmoc-FF)doped phthalocyanine (octakis(carboxyl)phthalocyanine zinc complex (Pc)) molecules, which provided a new way to regulate the supramolecular structure of dipeptides. [68] Xin et al studied the assembly of atomically precise silver NCs (Ag 9 -NCs, [Ag 9 (mba) 9 ] where H 2 mba = 2-mercaptobenzoic acid) and peptide DD-5, which showed CPL and realized temperature sensing and arginine detection. [69] Yang et al demonstrated opposite CPL signals at different pH values by characterizing the co-assembly process of tolane-substituted Phe-Phe dipeptides and 1,2-diaminoethan at different pH values.…”
Section: Cpl Materials Based On Amino Acids Peptides and Proteinsmentioning
confidence: 99%
“…116 Some of them can be assembled into nanomaterials with circularly polarized luminescence (CPL), which provide new strategies in 3D displays, optical data storage and biosensors. 117 In particular, porphyrin–polypeptide derivatives have been extensively studied as photosensitizers for photodynamic therapy. Here, we will introduce some typical applications such as simulated photosynthesis, photocatalysis, and biomedical applications.…”
Section: Functional Applications Of Porphyrin–peptide Assembliesmentioning
confidence: 99%